Optimality conditions for asymptotically stable control processes - Fernando Lobo Pereira (2006)
In this article, we present and discuss the infinite horizon optimal controlproblem subject to stability constraints. First, we consider optimality conditionsof the Hamilton-Jacobi-Bellman type, and present a method to define a feedbackcontrol strategy. Then, we address necessary conditions of optimality in the form ofa maximum principle. These are derived from an auxiliary optimal control problemwith mixed constraints.